Extremely cute animals operating heavy machinery - Gordon, David, 1965 January 22- (New York : Simon & Schuster Books for Young Readers, 2016)
When bullies try to stop the extremely cute animals from building their sand castle they band together to build something bigger and better.
AD 580
Accelerated Reader AR
Keywords: Animals -- Fiction; Bullying -- Fiction; Play -- Fiction; Animals -- Fiction; Bullying -- Fiction; Play -- Fiction